AM FUNGI AND MINE SPOIL CONSORTIUM: A MICROBIAL APPROACH FOR ENHANCING PROSO MILLET BIOMASS AND YIELD - CHANNABASAVA. A; H.C.LAKSHMAN (International Journal of Pharma and Bio Sciences, 2012)
Proso millet (Panicum miliaceum L.) was grown with inoculation of four indigenous AM fungal species in presence of different levels of mine spoil under green house conditions. The growth parameters such as biomass production, grain yield, per cent root infection and number of viable AM fungal spores in the rhizosphere of the mycorrhizal proso millet grown with 25% mine spoil were higher over the remaining treatments. The consortium of indigenous AM fungus Acaulospora laevis and mine spoil (25%) have supported significant growth of Proso millet compared to same concentration of mine spoil with other indigenous AM fungal inoculation. Higher levels of mine spoil (50% and 75%) affects on the growth and development of both AM fungi and experimental plant. The present work is an attempt towards utilization of mine spoil for the augmentation of mycorrhizal plant growth and it can be considered as eco-friendly management of mine spoil.